DERADIKALISASI DALAM MENANGGULANGI PAHAM RADIKALISME DAN TERORISME DI INDONESIA - Nugroho, Bakhtiar; Sudarto (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
The use of a hard approach as an effort to arrest, prosecute and enforce the law carried out by security forces against perpetrators of terror must be balanced with a soft approach in dealing with radicalism. Therefore, it is very interesting and important to study further whether terrorists exposed to radicalization can be neutralized with a deradicalization program? and how does deradicalization deal with radicalism and terrorism in Indonesia? To answer these problems, normative juridical legal research methods are used with statutory and conceptual regulatory approaches. Data obtained from primary, secondary and tertiary legal material sources were collected and then analyzed using qualitative data analysis techniques. From the research results, it was found that deradicalization is a strategy based on a conceptual understanding to deal with problems related to the development of ideologies and acts of radicalism. Deradicalization efforts must involve the government together with Indonesian civil society, especially to stop, eliminate, or at least neutralize radicalism. Deradicalization is a change with the modernization of radical ideology accompanied by a reasonable and integrated approach to social welfare. Efforts to modernize radical ideology are intended so that former perpetrators of terrorism, apart from no longer having radical beliefs, can also become agents of change that support the eradication of criminal acts of terrorism. Efforts to carry out deradicalization involving Indonesian civil society are needed as an effort to strengthen the ideological defense of citizens. Strengthening regulations by creating a separate law related to deradicalization to give it strength as a clear legal basis.